Spatiotemporal evolution of single sandbodies controlled by allocyclicity and autocyclicity in the shallow-water braided river delta front of an open lacustrine basin - Tong Qiang (Open Geosciences, 2021)
The spatial and temporal evolution of the sandbody architecture of shallow-water deltas in open lacustrine basins is controlled by the classification of allocyclicity and autocyclicity. On the southwestern margin of the Ordos Basin, a braided river system deposited a shallow-water delta in the Late Triassic Period. Based on the principle of sequence stratigraphy and the hierarchical analysis of reservoir architecture, the spatial and temporal evolution of individual sandbodies in the Chang 81 member of the Yanchang Formation in the Zhenbei Oilfield is interpreted by utilizing data from cores, wells and outcrops. The research ideas are as follows: large deposition scale architectural elements (first- to third-order cycles, as defined by Miall) of different sequence levels are affected by allocyclicity associated with changes in tectonic activity, provenance, and sea level, and small deposition scale architectural elements (fourth- to fifth-order cycles, as defined by Miall) of different sedimentary facies mainly consist of individual sandbodies that are affected by autocyclicity associated with lake-level changes caused by various river processes. Based on previous studies, the results are as follows. The sedimentary characteristics of shallow-water deltas have been verified by core and outcrop data. In addition, three ultrashort-term cycles are identified on the basis of boundary sequences and lithofacies’ sequences in the outcrop section of the Rui River, and three sedimentary evolution stages of the delta front are defined. Finally, according to well data, five types of architectural elements at the level of single sandbodies are identified. The vertical superimposition and lateral contact relationships of different architectural elements indicate that during the three sedimentary evolution stages, the hydrodynamics weakened, strengthened slightly, and finally weakened substantially. Among the 20 kinds of architectural element spatial combination patterns formed by single sandbodies, primary and secondary sandbodies have great potential for hosting remaining oil. In the process of architectural spatiotemporal evolution, the geometry and connectivity of the underwater distributary channel gradually weakened, and the spatial relationship between the underwater distributary channel and other architectural elements increased. This article proposes a new method for researching shallow-water deltas and has some guiding significance for exploiting the remaining oil in oil fields.